EFFECTS OF LOCAL HYPOXIA ON HEMATOLOGICAL PARAMETERS IN ATHLETES - PAUL, Alexis; BULDUȘ, Codruța-Florina (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Introduction: One of the key components of aerobic capacity is the hemoglobin quantity in the blood. Naturally, the body produces the erythropoietin, which promotes the synthetization of red blood cells, in states of tissue hypoxia. Aim: The Aim of this study is to investigate the effects the blood flow restriction at muscular level in athletes has on hemoglobin blood concentration. Objective: The objectives of this study are to create and to implement a training program based on blood flow restriction at muscular level to augment muscle performance in athletes. Material and methods: This method suggests the obstruction of blood flow to the legs using wrapped elastic bands at the superior area of the legs during running. For this study has been used as subject a young male footballer, being 19 years old, and the duration of this study case took 6 weeks. The training method consisted of sets of around 3 min of running adding up to 22-25 mins in total per training. In the first 4 weeks the subject completed on average 4.5 training sessions/week and in the last 2 weeks he completed 12 training sessions/week. Blood tests have been done at the beginning of the study, after 4 weeks of study and after 6 weeks of study. Results: After the first 4 weeks blood samples were taken and the results showed an increase in hematological values including hemoglobin, +0.3 g/dL, hematocrit, +2.5%. At the end of the 6 weeks, the blood samples showed a slight decrease in some hematological values compared to the ones at 4 weeks. Also, the results suggested modifications regarding the structure of the red cells. Discussion: The hematological modifications attained through this method can be compared with the results of other known methods such as blood transfusion or high-altitude training. Conclusion: This method caused improvements in the hematological values and of the VO2 MAX.